DEVELOPMENT OF A COMMUNITY HEALTH MONITORING INFORMATION SYSTEM IN PALELEH DISTRICT - Bumbuluto, Angki; Syafri Tuloli, Mohamad; Dwinanto, Arif (Gorontalo State University, 2025)
It is hoped that this system can overcome various problems in recording and registering public health, as well as making it easier to carry out health checks and access health history. Health monitoring is a very important thing to do so that the government can determine what actions or medical assistance will be prioritized, therefore a